Mesenchymal Stem Cells and Their Extracellular Vesicles: A Potential Game Changer for the COVID-19 Crisis - Kassem, Dina H.; Kamal, Mohamed M. (Frontiers in Cell and Developmental Biology, 2020)
Corona virus disease 2019 (COVID-19) is a global public health crisis. The high infectivity of the disease even from non-symptomatic infected patients, together with the lack of a definitive cure or preventive measures are all responsible for disease outbreak. The severity of COVID-19 seems to be mostly dependent on the patients’ own immune response. The over-activation of the immune system in an attempt to kill the virus, can cause a “cytokine storm” which in turn can induce acute respiratory distress syndrome (ARDS), as well as multi-organ damage, and ultimately may lead to death. Thus, harnessing the immuno-modulatory properties of mesenchymal stem cells (MSCs) to ameliorate that cytokine-storm can indeed provide a golden key for the treatment of COVID-19 patients, especially severe cases. In fact, MSCs transplantation can improve the overall outcome of COVID-2019 patients via multiple mechanisms; first through their immuno-modulatory effects which will help to regulate the infected patient inflammatory response, second via promoting tissue-repair and regeneration, and third through their anti-fibrotic effects. All these mechanisms will interplay and intervene together to enhance lung-repair and protect various organs from any damage resulting from exaggerated immune-response. A therapeutic modality which provides all these mechanisms undoubtedly hold a strong potential to help COVID-19 patients even those with the worst condition to hopefully survive and recover.